DEVELOPMENT OF AN AUTONOMOUS SYSTEM FOR CONTROL OF THE IRRIGATION REGIME OF AGRICULTURAL PRODUCTION IN A GREENHOUSE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Water is known to be a chemical compound and plays an essential role in sustaining life on our planet. Fresh water on earth is only 2.5% and the problems with the drought of the regions are known. Therefore, its sparing use will contribute to reducing this effect. This requires the revision of some of the policies of the agricultural sector and the implementation of new and innovative irrigation solutions. Through irrigation and their root system, plants grow and develop. The application of a proper irrigation regime will contribute to a reduction in water use. In this study, an attempt has been made to create an autonomous system for determining and applying the irrigation regime of plants. For this purpose, a greenhouse was used for the industrial production of cucumbers. A soil moisture sensor is used, and the signal is processed by software developed for this purpose, which produces a control signal for the beginning and end of the irrigation process. The process is controlled autonomously, depending on the current state of humidity and when a certain value is reached, the process is terminated. The sensor part is made of standard soil moisture sensors, and the control part is entrusted to a single-board computer with the ability to control via a wireless network.